2007
DOI: 10.1021/ol070456m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Perfluoroalkylated Benzenes and Pyridines through Cationic Rh(I)/Modified BINAP-Catalyzed Chemo- and Regioselective [2 + 2 + 2] Cycloaddition

Abstract: A convenient synthesis of perfluoroalkylated benzenes and pyridines has been achieved by a cationic Rh(I)/modified BINAP-complex-catalyzed chemo- and regioselective [2 + 2 + 2] cycloaddition of alkynes with a perfluoroalkylacetylene and a perfluoroalkylnitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Starting Materials: Diynes 1a, [32] 1b, [11c] 1c, [25g] 1d, [33] 1e, [32] 1g, [34] 1i, [35] 1j, [35] and 1k [3] and carbonyl compounds 2e, [36] 8c, [37] 8e, [38] and 8f [18] were prepared according to literature procedures. Anhydrous CH 2 …”
Section: Experimental Section General Methodsmentioning
confidence: 99%
“…Starting Materials: Diynes 1a, [32] 1b, [11c] 1c, [25g] 1d, [33] 1e, [32] 1g, [34] 1i, [35] 1j, [35] and 1k [3] and carbonyl compounds 2e, [36] 8c, [37] 8e, [38] and 8f [18] were prepared according to literature procedures. Anhydrous CH 2 …”
Section: Experimental Section General Methodsmentioning
confidence: 99%
“…The selectivity of this reaction has been rationalized by considering the steric repulsion between the metallacyclopentadiene intermediate and the nitrile. Several examples that might be explained in terms of the electronic nature of the diyne substrate (and that of the corresponding metallacycle intermediates) have been reported by Schreiber and coworkers, 9 Tanaka et al,3c,10 Louie and co-workers, 11 and our research group 12 for reactions catalyzed by CpCo(CO) 2 , cationic diphosphine-rhodium, N-heterocyclic carbene (NHC)-nickel, or diphosphine-cobalt systems, respectively. Here we report a regioselective [2+2+2] cycloaddition of diynes with nitriles catalyzed by a 1,2-bis(diphenylphosphino)ethane-cobalt(II) chloride hexahydrate-zinc [(dppe)CoCl 2 ·6H 2 O-Zn] reagent, 12 and we discuss the relationship between the selectivity and the substrate structure.…”
mentioning
confidence: 64%
“…In contrast, when 2-cyanopyridine (2d) was used, the regiochemistry of the product was completely changed by the substituent on the diyne 1 (Table 4, entries [10][11][12]. Once more, we observed that, in terms of the regioselectivity, the relatively electron-deficient nitrile 2d was much more sensitive to the electronic nature of the diyne than were the other nitriles.…”
Section: Methodsmentioning
confidence: 95%
“…3,4 For example, our research group found in 2003 that a cationic rhodium(I)/H 8 -BINAP complex catalyzes the intermolecular crosscyclotrimerization of terminal alkynes and symmetrical internal alkynes (dialkyl acetylenedicarboxylates). 4,5 After this Letter, the intermolecular cross-cyclotrimerization of terminal alkynes with unsymmetrical internal alkynes (alkynoates) has also been accomplished using perfluoroalkylacetylene 6 and aryl ethynyl ethers 7 as terminal alkynes, 8 and the cationic rhodium(I)/H 8 -BINAP complex as a catalyst. In this Letter, we have established that a cationic rhodium(I)/BIPHEP complex is capable of catalyzing the intermolecular cross-cyclotrimerization of silylacetylenes and unsymmetrical electron-deficient internal alkynes (alkynoates and an alkynone).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the rhodacycle generated from the alkynoate, in which the alkoxycarbonyl group is located in the a-position to rhodium, is preferable as a result of the coordination of the carbonyl group to rhodium. 6 Therefore, generation of regioisomers 3 and 4 from rhodacycles C and D, respectively, is more preferable than that from rhodacycle E, in which the alkoxycarbonyl group is located in the b-position to rhodium.…”
Section: Introductionmentioning
confidence: 99%